ZBTB24 (Zinc Finger and BTB Domain Containing 24) prevents recurrent spontaneous abortion by promoting trophoblast proliferation, differentiation and migration. Issue 2 (1st February 2022) - Ruan, Haibo; Dai, Zhenzhen; Yan, Jinyu; Long, Xiaoxi; Chen, Yi; Yang, Youlin; Yang, Qian; Zhu, Jun; Zheng, Meiyun; Zhang, Xiahui
ABSTRACT: Recurrent spontaneous abortion (RSA) is a common complication during early gestation, which is associated with aberrant DNA methylation. Zinc Finger and BTB Domain Containing 24 (ZBTB24) plays a critical role in facilitating DNA methylation and cell proliferation. However, the regulatory role of ZBTB24 on trophoblast development in RSA remains unclear. In this study, ZBTB24 expression was compared between decidua tissues of RSA patients and induced abortion controls from a published dataset, which was further validated in placental villi tissues by RT-qPCR and Western blot. The roles of ZBTB24 in trophoblast proliferation, differentiation, and migration were investigated by functional assays after ZBTB24 knockdown or overexpression in HTR-8/SVneo cells. Our results showed that ZBTB24 expression was significantly decreased in RSA patients, and ZBTB24 expression level positively regulated cell viability, differentiation, and migration in HTR-8/SVneo cells. We further demonstrated that ZBTB24 modulated the expression of E-cadherin by altering the DNA methylation at the promoter region. Overall, the downregulation of ZBTB24 is implicated in RSA by inhibiting trophoblast proliferation, differentiation, and migration. Therefore, ZBTB24 may serve as a promising therapeutic target and diagnostic marker for RSA.